An excited state dynamics driven reaction: wavelength-dependent photoisomerization quantum yields in [Ru(bpy)2(dmso)2]2+. Issue 22 (27th May 2020) - Livshits, Maksim Y.; Wang, Lei; Vittardi, Sebastian B.; Ruetzel, Stefan; King, Albert; Brixner, Tobias; Rack, Jeffrey J.
Abstract : We report the excited-state behavior of a simple bis -sulfoxide complex, cis -S, S-[Ru(bpy)2 (dmso)2 ] 2+, as investigated by femtosecond pump–probe spectroscopy. Abstract : We report the excited-state behavior of a structurally simple bis -sulfoxide complex, cis -S, S-[Ru(bpy)2 (dmso)2 ] 2+, as investigated by femtosecond pump–probe spectroscopy. The results reveal that a single photon prompts phototriggered isomerization of one or both dmso ligands to yield a mixture of cis -S, O-[Ru(bpy)2 (dmso)2 ] 2+ and cis -O, O-[Ru(bpy)2 (dmso)2 ] 2+ . The quantum yields of isomerization of each product and relative product distribution are dependent upon the excitation wavelength, with longer wavelengths favoring the double isomerization product, cis -O, O-[Ru(bpy)2 (dmso)2 ] 2+ . Transient absorption measurements on cis -O, O-[Ru(bpy)2 (dmso)2 ] 2+ do not reveal an excited-state isomerization pathway to produce either the S, O or S, S isomers. Femtosecond pulse shaping experiments reveal no change in the product distribution. Pump–repump–probe transient absorption spectroscopy of cis -S, S-[Ru(bpy)2 (dmso)2 ] 2+ shows that a pump–repump time delay of 3 ps dramatically alters the S, O : O, O product ratio; pump–repump–probe transient absorption spectroscopy of cis -O, O-[Ru(bpy)2 (dmso)2 ] 2+ with a time delay of 3 ps uncovers an excited-state isomerization pathway to produce the S, O isomer. In conjunction with low-temperature steady-state emission spectroscopy, these results are interpreted in the context of an excited-state bifurcating pathway, in which the isomerization product distribution is determined not by thermodynamics, but rather as a dynamics driven reaction.